CD4+ Tumor infiltrating lymphocytes are prognostic and independent of R‐IPI in patients with DLBCL receiving R‐CHOP chemo‐immunotherapy. Issue 4 (5th March 2013) - Keane, Colm; Gill, Devinder; Vari, Frank; Cross, Donna; Griffiths, Lynn; Gandhi, Maher
<x xml:space="preserve">Abstract</x> Despite the Revised International Prognostic Index's (R‐IPI) undoubted utility in diffuse large B‐cell lymphoma (DLBCL), significant clinical heterogeneity within R‐IPI categories persists. Emerging evidence indicates that circulating host immunity is a robust and R‐IPI independent prognosticator, most likely reflecting the immune status of the intratumoral microenvironment. We hypothesized that direct quantification of immunity within lymphomatous tissue would better permit stratification within R‐IPI categories. We analyzed 122 newly diagnosed consecutive DLBCL patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP) chemo‐immunotherapy. Median follow‐up was 4 years. As expected, the R‐IPI was a significant predictor of outcome with 5‐year overall survival (OS) 87% for very good, 87% for good, and 51% for poor‐risk R‐IPI scores (P < 0.001). Consistent with previous reports, systemic immunity also predicted outcome (86% OS for high lymphocyte to monocyte ratio [LMR], versus 63% with low LMR, P = 0.01). Multivariate analysis confirmed LMR as independently prognostic. Flow cytometry on fresh diagnostic lymphoma tissue, identified CD4+ T‐cell infiltration as the most significant predictor of outcome with ≥23% infiltration dividing the cohort into high and low risk groups with regard to event‐free survival (EFS, P = 0.007) and OS (P = 0.003). EFS and OS were independent of the R‐IPI and LMR. Importantly, within very good/good R‐IPI patients, CD4+ T‐cells still distinguished patients with different 5 year OS (high 96% versus low 63%, P = 0.02). These results illustrate the importance of circulating and local intratumoral immunity in DLBCL treated with R‐CHOP. Am. J. Hematol. 88:273–276, 2013. © 2013 Wiley Periodicals, Inc.